The Application of Problem Based Learning Model to Improve Learning Outcomes of Third Grade Students at SDK St. Yoseph Noelbaki on Data Presentation Material for the 2024/2025 - bara, Ayu Apriyani (Journal of Character and ELementary Education, 2025)
This study aims to improve student learnin outcomes through the application of problem based learning models on data presentation materials, the subjects in this study were 24 students of grade 3 of elementary school st yoseph noelbaki. The method used ini this study is sclass room action research (PTK) model kemmis and tagarth whichconsists of planning, action, observation and reflection. The data collection tecniqus used in this study were observation, testing, and documentation. Teknik analisis data ini meliputi 3 tahap yaitu: (1) reduksi data (2) penyajian data (3) penarikan kesimpulan dan verifikasi. The results of the study showed that through the application of problem based learning models, learning outcomes can be improve. It is known that the learning outcomes in cyle 1 the percentage of completeness is 29,17%,afte the action is taken cycle 2 the percenage of completeness reaches 79,17%. Thus it is concluted that the application of problem based learning models can improve student learning outcomes.